DIFERENSIASI POSITIONING TERHADAP KEPUTUSAN PEMBELIAN SILKY PUDDING BERDASARKAN PREFERENSI KONSUMEN DI JABODETABEK (STUDI KASUS: PADA BOMBOM PUDING, GYUKAKU PUDING DAN PUYO) - Siti Iqlima Keisha Aliya Putri Saepuloh; Firly Rahma Ekaputri; Elri Frella Natasya; Stephanny Lianardo (PT. Hasba Edukasi Mandiri, 2025)
This study aims to analyze consumer perceptions of three silky pudding brands—Bombom, Gyukaku, and Puyo—using the Multidimensional Scaling (MDS) method. This research is crucial for understanding brand positioning differentiation based on product attributes perceived by consumers. The sample consists of 37 respondents selected through purposive sampling, specifically individuals who have tried at least two of the three pudding brands under study. Data were collected using a closed-ended questionnaire based on a Likert scale, covering nine product attributes such as taste, texture, packaging, price, and accessibility. The collected data were analyzed using SPSS through MDS testing to map the relative position of each product based on dominant attributes. The test results show a stress value of 0.04807 and an RSQ of 0.99144, indicating a highly reliable configuration. Findings reveal that Puyo excels in packaging and branding, Bombom is perceived to be superior in taste and price, while Gyukaku stands out in terms of texture and satisfaction. The resulting perceptual map provides a clear visualization of brand differentiation, which can serve as the foundation for strategic marketing recommendations. This study concludes that strong brand positioning differentiation plays a vital role in influencing consumers' purchase decisions for silky pudding.